VARIASI PEMAKAIAN KATA DALAM ACARA INI TALK SHOW DI NET TV - Oktavianita Oktavianita; Basuki Basuki (CARAKA, 2020)
The purpose of this study (1) Describe variations of word usage in the program This Talk Show on NET TV. (2) Describe the meaning of using words in the program This Talk Show on NET TV. (3) Describe the word usage function in the program This Talk Show on NET TV. This type of research is a qualitative descriptive study. The data in this study are in the form of sentences containing variations in the use of words in the program Talk Show on NET TV. This data is sourced from the use of language in the program This Talk Show on NET TV. The method of data collection in this study uses the method of listening with the ability to engage in competent free and recorded techniques. Data analysis methods used in this study are the matching method and the method of sharing. The equivalent method is translational and pragmatic equivalent. The method of presenting the results of data analysis uses the informal presentation method. The results of this study are (1) Variations in the use of words in the program Talk Show on NET TV include (a) phonological variations, (b) morphological variations, (c) variations seen from the origin of language. (2) meaning of word usage in this program Talk Show on NET TV includes (a) connotative meaning, (b) denotative meaning, (c) idiomatic meaning. (3) the word usage function in this Talk Show program on NET TV includes (a) the fatigue function, (b) the referential function, and (c) the emotive function.